(untitled) - Werner, Patricia K. (New York, 1996)
Mosaic Two is designed for students who are at a high-intermediate to advanced level of English proficiency. Students at this level typically begin the course scoring 480 and above on the TOEFL. They are comfortable in most conversational settings, but may still have problems understanding spoken English, especially in rapid or heated discussions. The may have some fossilized errors in spoken English and may lack the range of vocabulary needed for complex situations. They typically can read authentic material with a high degree of comprehension and speed, but may have problems with both speed and understanding when dealing with complex material on unfamiliar topics. Writing skills are strong, but again, they may have difficulty dealing with complex material. New to this Edition: Chapter 8 in all books features a new theme, "Breakthroughs". Most chapters include new "Focus on Testing" boxes, which offer tips and suggestions to better prepare students for taking quizzes and tests, including standardized tests such as the TOEFL. A new layout and two-color design makes the books easier to use. Updated, expanded photos, drawings, and realia facilitate learning. An exciting new video program accompanies this edition; segments provide authentic content from network news programming and correspond to the chapter themes in all four texts. A new book, A Video Guide, features exercises and activities to use with the new video. The revised Instructor's Manual/Test Bank offers more testing materials, including a new placement test for the entire five-level program.
Keywords: English language,English language,Listening; Spoken english,Problems, exercises, etc,Textbooks for foreign speakers,Problems, exercises, etc